Functional optoacoustic neuro-tomography for scalable whole-brain monitoring of calcium indicators - Dean-Ben, X. Luis; Sela, Gali; Lauri, Antonella; Kneipp, Moritz; Ntziachristos, Vasilis; Westmeyer, Gil G.; Shoham, Shy; Razansky, Daniel (Light: Science & Applications, 2016)
Non-invasive observation of spatiotemporal activity of large neural populations distributed over entire brains is a longstanding goal of neuroscience. We developed a volumetric multispectral optoacoustic tomography platform for imaging neural activation deep in scattering brains. It can record 100 volumetric frames per second across scalable fields of view ranging between 50 and 1000 mm3 with respective spatial resolution of 35-200 μm. Experiments performed in immobilized and freely swimming larvae and in adult zebrafish brains expressing the genetically encoded calcium indicator GCaMP5G demonstrate, for the first time, the fundamental ability to directly track neural dynamics using optoacoustics while overcoming the longstanding penetration barrier of optical imaging in scattering brains. The newly developed platform thus offers unprecedented capabilities for functional whole-brain observations of fast calcium dynamics; in combination with optoacoustics' well-established capacity for resolving vascular hemodynamics, it could open new vistas in the study of neural activity and neurovascular coupling in health and disease.
CRIS-Team Scopus Importer:2023-03-08
Keywords: functional neuro-imaging; genetically encoded calcium indicators; high spatiotemporal resolution; large-scale brain activity; optoacoustic tomography; photoacoustics; real-time imaging